2019
DOI: 10.5334/dsj-2019-022
|View full text |Cite
|
Sign up to set email alerts
|

The Definition of Reuse

Abstract: The ability to reuse research data is now considered a key benefit for the wider research community. Researchers of all disciplines are confronted with the pressure to share their research data so that it can be reused. The demand for data use and reuse has implications on how we document, publish and share research in the first place, and, perhaps most importantly, it affects how we measure the impact of research, which is commonly a measurement of its use and reuse. It is surprising that research communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 30 publications
2
21
0
5
Order By: Relevance
“…In this section, we move towards a researcher-centered definition of reproducibility that reflects common concerns of researchers. This approach is in line with findings from van de Sandt et al [188] who analyzed differences between use and reuse in science. They concluded that differences in those terminologies often do not reflect scientific realities and proposed to refer only to scientific use.…”
Section: Towards a Researcher-centered Definition Of Reproducibilitysupporting
confidence: 87%
“…In this section, we move towards a researcher-centered definition of reproducibility that reflects common concerns of researchers. This approach is in line with findings from van de Sandt et al [188] who analyzed differences between use and reuse in science. They concluded that differences in those terminologies often do not reflect scientific realities and proposed to refer only to scientific use.…”
Section: Towards a Researcher-centered Definition Of Reproducibilitysupporting
confidence: 87%
“…Not many studies have formally defined the term reuse. van de Sandt, Dallmeier-Tiessen, Lavasa, & Petras (2019) argued that the term reuse is a complicated concept and no common definition is proposed across the disciplines yet. Despite the difficulties of proposing agreed definition across the disciplines, researchers generally understand it to indicate the use of data by someone who did not collect it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This may be due to the long history of having data reuse practice in the field of health and social science (Clubb, Austin, Geda, & Traugott, 1985). Also, as the previous literature suggested ( van de Sandt, et al, 2019), because the term referred data reuse were varied across the disciplines, other disciplines may not use the term "data reuse" or "secondary data" even when reusing data. Most of them (80.7%) were Caucasian.…”
Section: Participantsmentioning
confidence: 99%
“…While the definition of data reuse is a matter of discussion (see van de Sandt, Dallmeier-Tiessen, Lavasa, & Petras, 2019), broadly speaking, data reuse relates to the " […] research in which some or all of the data analyzed were collected by others besides the reuser or members of his/her research team" (Curty, Crowston, Specht, Grant, & Dalton, 2017). Such definitions of data reuse are often based on the assumption that the reuser is part of a specific designated community (as defined by the Open Archival Information System, 2012), usually, a part of the scientific community.…”
Section: Introductionmentioning
confidence: 99%